Indonesian Capital Market Reaction To The Announcement Of A Recession Due To The Pandemic Covid-19: Reaksi Pasar Modal Indonesia Terhadap Peristiwa Pengumuman Resesi Akibat Pandemi Covid-19 - Vani Aryani; Nurasik (Academia Open, 2021)
On November 5, 2020, Indonesia was declared a recession after the Central Statistics Agency announced that the Indonesian economy experienced a decline in the third quarter of 2020. The Indonesian economy experienced a decline in the third quarter of 2020, which was minus 3.49 percent. In the second quarter of 2020, the Indonesian economy was already minus 5.32 percent. The announcement of the recession event gave rise to various perceptions for capital market participants. So the purpose of this study is to find out and compare the differences in the average Abnormal Return, Trading Volume Activity, and Security Return Variability of IDX 30 issuers before and after the announcement of the recession due to the COVID-19 pandemic. The research method used is quantitative research with an event study approach. The type of data in this study is secondary data with data collection techniques using the documentation method. The sample used is IDX30 stock issuers on the Indonesia Stock Exchange for the period August 2020 - January 2021. The data analysis technique in this study is descriptive statistical analysis, paired t-test and Wilcoxon signed rank test. The results of this study indicate that: (1) there is a significant difference in the average abnormal return of IDX 30 issuers before and after the announcement of the recession due to the covid-19 pandemic. (2) there is a significant difference in the average Trading Volume Activity of IDX 30 issuers before and after the announcement of the recession due to the covid-19 pandemic. (3) there is no significant difference in the average Security Return Variability of IDX 30 issuers before and after the announcement of the recession due to the covid-19 pandemic.